Dimensionamento e construção de um sistema de aeração em um protótipo de silo - aerador armazenador - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The work aims at the design and construction of a prototype of a 100% functional aeration system in a grain storage silo, on a reduced scale (1:50) with 40 cm in diameter and 60 cm in height, which would represent in scale a real silo 20 meters in diameter and 30 meters high. The construction was carried out using concrete at its base, with the aeration ducts embedded in it, and galvanized sheet metal to make the body of the storage silo and the cover. It was dimensioned following norms and methodologies currently applied for the construction of full-scale silos. Firstly, the design of the storage system was carried out, where data from the wheat crop were adopted for this design, since this is the crop that has the highest specific mass value among other cultures, with this it is possible to guarantee that the prototype will withstand store and aerate any other desired crop safely and efficiently. To carry out the air insufflation in the aeration system, a centrifugal fan was designed and built, using 2 mm PVC sheet for the body of the volute, this being in a scale proportional to the prototype, which efficiently meets the flow rate required by the system. The prototype built will be available at the Post Harvest Laboratory (LAPÓS), at Unipampa, Campus Alegrete, which will be used for demonstration in practical classes and future work by the students.
Keywords: Engenharia agrícola; Protótipo; Aeração de grãos; Grãos - Armazenamento; Agricultural engineering; Prototype; Grain aeration; Grains - Storage; CNPQ::CIENCIAS AGRARIAS